Нецукровий діабет як маска іншого захворювання - Юзвенко, Т. Ю.; Гирявенко, О. Я.; Чуприна, Л. О.; Балуєва, С. О. (Clinical Endocrinology and Endocrine Surgery, 2011)
The article described a case of psychogenic polydipsia in a patient K., a differential diagnostics of this disease with diabetes insipidus.